Penguatan Literasi Digital Berbasis Etika Bermedia Sosial Sebagai Strategi Pengembangan SDM Pelajar di Kalimantan Timur dalam Menangkal Hoaks - Ulul Azmi Mustari; Shinta Purnama Sari (Badan Pengembangan Sumber Daya Manusia Provinsi Kalimantan Timur, 2025)
The lack of digital literacy among students leads to a lack of understanding regarding social media ethics, even though social media ethics is very important because students use social media every day, which certainly contains various kinds of hoax information. If this is not handled properly, students will be easily influenced and even spread the hoax news. Therefore, this study aims to describe the role of digital literacy in shaping the social media ethics of vocational high school students to prevent the spread of hoax news. This study is a qualitative study with a descriptive analysis approach. To collect data, observation, interviews, and documentation were used. The results of the study indicate that digital literacy plays a significant role in shaping the social media ethics of vocational high school students, especially in preventing the spread of hoax news. Student perspectives show that understanding of digital literacy is still diverse, but schools play a significant role in increasing their digital awareness and skills through various educational programs. Intensive social media use among students requires the implementation of good media ethics, such as critical attitudes, responsibility, and respect for the truth of information. The spread of hoax news is understood as a form of unethical behavior that can harm oneself and others, so effective prevention strategies are needed, such as improving information verification skills, regular counseling, and strengthening students’ character through education based on digital ethical values.